Identifikasi Anemia, Kekurangan Energi Kronis, dan Penyuluhan Gizi pada Remaja Putri di SMA Negeri 3 Kendari - Toruntju, Sultan Akbar; Gani, Kameriah; Rofiqoh, Rofiqoh (PT Karya Inovasi Berkelanjutan, 2025)
Nutrition education is a comprehensive process aimed at changing community behavior so that healthy dietary habits can be applied in daily life. Understanding the local nutritional status supports the implementation of nutrition education programs that can lead to positive changes in knowledge, attitudes, and behaviors related to food and nutrition. This community service activity aimed to identify the prevalence of nutritional problems, specifically anemia and chronic energy deficiency (CED), and subsequently provide nutrition counseling to adolescents. The program was conducted at SMA Negeri 3 Kendari in August 2023, involving 92 female students from grades 10 and 11. The activities were carried out over two days: on the first day anthropometric measurements and blood sampling (hemoglobin testing) were performed, while the second day was dedicated to nutrition counseling. The results showed that 67.3% of students suffered from CED and 42.6% from anemia. Post-counseling evaluation indicated that the majority of participants (78.3%) demonstrated sufficient nutrition knowledge. These findings suggest that school-based direct nutrition education interventions are an effective strategy for improving the nutrition knowledge of adolescent girls, particularly those experiencing CED and anemia. Such interventions should be implemented continuously and expanded to other schools. Collaboration between schools and health professionals is recommended to integrate nutrition education into regular school programs, including periodic monitoring of nutritional status and hemoglobin levels. Achieving Sustainable Development Goals (SDGs) This community service activity focused on preventing nutritional problems among adolescent girls through screening for anemia and CED. The outcomes contribute to Sustainable Development Goal (SDG) 3: Ensure healthy lives and promote well-being for all at all ages. Specifically, it supports Target 3.4, which aims by 2030 to reduce premature mortality from non-communicable diseases by one-third through prevention and treatment, and to promote mental health and well-being.